ChemInform Abstract: Heteroarylboronates in Rhodium‐Catalyzed 1, 4‐Addition to Enones. Issue 12 (March 2015) - Albrecht, Fabian; Sowada, Oliver; Fistikci, Meryem; Boysen, Mike M. K.
Abstract The 1, 4‐addition of heteroaryl MIDA and pinacol boronates (II) and (IV) as alternative to labile boronic acid counterparts is studied.